Siglecs in Brain Function and Neurological Disorders - Shoib Sarwar Siddiqui; Rachel Matar; Maxime Merheb; Rawad Hodeify; Cijo George Vazhappilly; John Marton; Syed Azharuddin Shamsuddin; Hussain Al Zouabi (Cells, 2019)
Siglecs (Sialic acid-binding immunoglobulin-type lectins) are a I-type lectin that typically binds sialic acid. Siglecs are predominantly expressed in immune cells and generate activating or inhibitory signals. They are also shown to be expressed on the surface of cells in the nervous system and have been shown to play central roles in neuroinflammation. There has been a plethora of reviews outlining the studies pertaining to Siglecs in immune cells. However, this review aims to compile the articles on the role of Siglecs in brain function and neurological disorders. In humans, the most abundant Siglecs are CD33 (Siglec-3), Siglec-4 (myelin-associated glycoprotein/MAG), and Siglec-11, Whereas in mice the most abundant are Siglec-1 (sialoadhesin), Siglec-2 (CD22), Siglec-E, Siglec-F, and Siglec-H. This review is divided into three parts. Firstly, we discuss the general biological aspects of Siglecs that are expressed in nervous tissue. Secondly, we discuss about the role of Siglecs in brain function and molecular mechanism for their function. Finally, we collate the available information on Siglecs and neurological disorders. It is intriguing to study this family of proteins in neurological disorders because they carry immunoinhibitory and immunoactivating motifs that can be vital in neuroinflammation.